2006
DOI: 10.1891/0047-2220.37.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Marital Satisfaction when a Spouse has Multiple Sclerosis

Abstract: The current study examines marital satisfaction from the perspective of a well spouse who is responsible for caregiving a spouse with Multiple Sclerosis (MS). Forty spouses of individuals with MS completed questionnaires. A multiple regression analysis was conducted to determine the relationship of love, satisfaction with physical intimacy, communication, and caregiver burden to marital satisfaction. Results indicated that love and communication were significantly positively related to marital satisfaction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The spouse studies examined the following areas: immune response (32); experience of care giving (33)(34)(35)(36)(37); psychological outcomes and QOL, including marital satisfaction (38)(39)(40)(41)(42)(43). Both qualitative (n = 6) and quantitative (n = 6) approaches were utilized, and together, they provide insight regarding the spousal dimension of care-giving and suggest that spouse carers have particular needs.…”
Section: Spouse Studiesmentioning
confidence: 99%
“…The spouse studies examined the following areas: immune response (32); experience of care giving (33)(34)(35)(36)(37); psychological outcomes and QOL, including marital satisfaction (38)(39)(40)(41)(42)(43). Both qualitative (n = 6) and quantitative (n = 6) approaches were utilized, and together, they provide insight regarding the spousal dimension of care-giving and suggest that spouse carers have particular needs.…”
Section: Spouse Studiesmentioning
confidence: 99%
“…Onset of the disease in early adulthood, right at the time of formation and maintenance of intimate relationships, marriage, childbearing and job status exacerbates its effect on components of interpersonal relationships (Beshears, 2010;McCabe, 2002), so that, research findings show that MS is associated with a significant reduction in the probability of marriage for single people and a sixfold increase in the risk of divorce in married women (Buchanan et al, 2010;Glantz et al, 2009). It can cause sexual dysfunction (Sevène et al, 2009) and can also reduce marital satisfaction, communication and physical intimacy in the couples (Perrone, Gordon, & Tschopp, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20]23 Furthermore, a variety of studies have also shown that caregiver burden may have a negative effect on people with MS (reciprocal effect) and the relationship between people with MS and their caregivers. 19,[21][22][23] Therefore, screening caregivers for early recognition of burden and how this might affect their health and well-being can help tailor interventions to improve caregiver health outcomes and work productivity and potentially mitigate the reciprocal caregiver burden effect. As described previously herein, caring for people with MS has a negative effect on employment status and work productivity among caregivers, and this has also been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…with MS (reciprocal effect) and the relationship between people with MS and their caregivers. 19,[21][22][23] Furthermore, caregiver burden has a negative effect on the work productivity of MS caregivers (ie, indirect work productivity loss). 24,25 Therefore, identifying potential factors that may contribute to reducing informal care requirements in MS, and targeting those that are modifiable, is important not only for people with MS and their caregivers but also from a societal perspective to reduce the societal costs associated with direct and indirect work productivity loss in MS.…”
mentioning
confidence: 99%